2020
DOI: 10.1021/acs.est.0c01456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracellular Polymeric Substances on the Formation and Methylation of Mercury Sulfide Nanoparticles

Abstract: Growing evidence has suggested that microbial biofilms are potential environmental “hotspots” for the production and accumulation of a bioaccumulative neurotoxin, methylmercury. Here, we demonstrate that extracellular polymeric substances (EPS), the main components of biofilm matrices, significantly interfere with mercury sulfide precipitation and lead to the formation of nanoparticulate metacinnabar available for microbial methylation, a natural process predominantly responsible for the environmental occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Field and laboratory studies have demonstrated the existence of biomethylation potentials of nano-HgS in environmental systems. The amount, surface structure, and size distribution of nanophase HgS can affect the transport, reactivity, and methylation potential of Hg in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Field and laboratory studies have demonstrated the existence of biomethylation potentials of nano-HgS in environmental systems. The amount, surface structure, and size distribution of nanophase HgS can affect the transport, reactivity, and methylation potential of Hg in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the central role of sulfide in Hg methylation (Graham et al ., 2012, 2013; Zhou et al ., 2017; Mazrui et al ., 2018; Thomas et al ., 2018; An et al ., 2019; Thomas et al ., 2019; Zhang et al ., 2020; Tian et al ., 2021). Most recently, Tian et al .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the central role of sulfide in Hg methylation (Graham et al, 2012(Graham et al, , 2013Zhou et al, 2017;Mazrui et al, 2018;Thomas et al, 2018;An et al, 2019;Thomas et al, 2019;Zhang et al, 2020;Tian et al, 2021). Most recently, Tian et al (2021) described the importance of Hg(II)-sulfides as a major driver of MeHg production.…”
Section: The Diffusion Of Gaseous H 2 S Makes Hg(ii) Bioavailablementioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, precipitation of inorganic divalent mercury and sulfide in the presence of natural organic matter (NOM) led to the formation of nanoparticulate mercury sulfide (HgS, i.e., metacinnabar) that was available for microbial methylation. [15][16][17] Considering that soil microorganisms can reduce selenate and selenite, i.e. the main components of Se-fertilizers, to selenide, [18][19][20][21] co-precipitation of mercuric mercury, selenide and NOM may represent as a potential pathway for forming bioavailable mercury species, particularly nano-HgSe, for MeHg production that induces severe ecological and health risks.…”
Section: Introductionmentioning
confidence: 99%